2019
DOI: 10.3329/bjms.v18i2.40684
|View full text |Cite
|
Sign up to set email alerts
|

The role of zinc supplementation for diarrhoea in children: a critical review

Abstract: Background: Nearly 1.7 million children suffer from diarrhoea and around 760,000 die each year. The high prevalence of diarrhoea in the developing countries is closely related to lack of safe drinking water, inadequate sanitation and hygiene, and poor health and nutritional status. These environmental conditions facilitate the spread of infectious disease easily. The great morbidity and mortality of this preventable and treatable disease raise concern on how to save children from this fatal disease by improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This is also supported by report of Nargis et al 41 where it was postulated that Sharbat Misali (an Unani preparation of hematinics) enhanced hemoglobin level and its safety supported by data obtained from study of hepatic and renal function. Even when nutrients are present in supplemental form, alleviation of symptoms of diseases can still occur (Putri et al) 42 The fact that SCD can be complicated by many other endemic diseases in Africa brings some urgency to our efforts in treating/managing sickle cell disease especially using nutritional and non-nutritional methods. For example, Prusty et al 43 identified that multiple splenic infarcts may result from sickle cell complication of Dengue fever.…”
Section: Resultsmentioning
confidence: 99%
“…This is also supported by report of Nargis et al 41 where it was postulated that Sharbat Misali (an Unani preparation of hematinics) enhanced hemoglobin level and its safety supported by data obtained from study of hepatic and renal function. Even when nutrients are present in supplemental form, alleviation of symptoms of diseases can still occur (Putri et al) 42 The fact that SCD can be complicated by many other endemic diseases in Africa brings some urgency to our efforts in treating/managing sickle cell disease especially using nutritional and non-nutritional methods. For example, Prusty et al 43 identified that multiple splenic infarcts may result from sickle cell complication of Dengue fever.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies showed that zinc supplementation play a significant role in children with acute diarrhoea by accelerating intestinal mucosa regeneration and supporting electrolyte transports. Related to the area of uncertainty, evidences show that zinc is significantly beneficial in children with acute diarrhoea (Crisinel et al, 2015;Patel et al, 2009;Putri et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Study documented that there is a lack of sanitation, regular water supply, drainage system and proper toilet 20 . These environmental circumstances favour the spread of different diseases 35 . Another study also indicated that poor sanitation is the major cause of typhoid, malaria, dermatitis manifestation, gastroenteritis, intestinal infections and encephalitis 20 .…”
Section: Hygiene Practicesmentioning
confidence: 99%